Rare bird documentation form for Greater Scaup at Montrose, 1983 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1983)
Rare bird documentation form for three Greater Scaups at Montrose in Lee County, IA on November 20, 1983. Epson - sheet feed